2018
DOI: 10.1155/2018/4539171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Overweight and Obesity among Somalis in Norway and Somaliland: A Comparative Study

Abstract: Background and Aim The knowledge about the health status of Somalis in Norway and Somaliland is limited. This paper reports the results of a comparative study on the prevalence and predictors of overweight/obesity among Somalis in Norway and Somaliland. Method We conducted two cross-sectional studies using the same tools and procedures, between 2015 and 2016. The study population was adults aged 20–69 years (n=1110 (Somaliland) and n=220 (Norway)). Results The prevalence of obesity (body mass index (BMI) ≥30 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
3
11
2
Order By: Relevance
“…The high proportion of overweight and obesity among women compared to men has been reported previously [13], and is consistent with other findings [31]. The high prevalence of overweight and physical inactivity in women are likely interrelated [32, 33], as physical inactivity is a risk factor for obesity and other chronic diseases [34].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high proportion of overweight and obesity among women compared to men has been reported previously [13], and is consistent with other findings [31]. The high prevalence of overweight and physical inactivity in women are likely interrelated [32, 33], as physical inactivity is a risk factor for obesity and other chronic diseases [34].…”
Section: Discussionsupporting
confidence: 89%
“…Data about NCDs and their risk factors in this region are scarce. We have previously reported that the prevalence of overweight and obesity was significantly higher among Somalis in Oslo, Norway compared to Hargeisa, Somaliland [13], and according to the Ministry of Health of Somaliland, unhealthy lifestyle, including physical inactivity, smoking and chewing khat, has led to an increase in NCDs [14]. Urbanization has been identified as a root cause of the increasing prevalence of NCDs and their risk factors in sub-Saharan Africa [15].…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, a large proportion of men and women are overweight and obese (61% and 78% respectively) (Ahmed. et al 2018), and the obesity rate is substantially higher among women than men (p < 0.001).…”
Section: Anthropometric Measurementssupporting
confidence: 54%
“…Somalis in Norway stand out as experiencing the most disadvantaged position by any socioeconomic standards, such as poor living conditions and unemployment, and they face a number of challenges, such as language barriers (Vrålstad and Wiggen 2017;Markussen 2018). We have recently reported that persons with Somali immigrant background in Oslo have low physical activity and high prevalence of overweight, obesity, and high waist circumference (Ahmed et al 2018;Ahmed et al 2019). These conditions can to lead to decreased health status.…”
Section: Introductionmentioning
confidence: 99%
“…Somali immigrants and refugees in the US and other Western countries have disproportionately higher rates of obesity and related cardiovascular disease risks, such as diabetes mellitus [6][7][8][9][10][11][12]. The higher rates have been postulated to result from the adoption of lifestyles that include low levels of physical activity and a diet rich in refined carbohydrates and fat [10,13,14]. In turn, these lifestyle and behavioral factors that promote the development of obesity are enabled by multiple, complex, and interconnected social and environmental factors [15,16].…”
Section: Introductionmentioning
confidence: 99%